The Peacock Fallacy: Art as a Veblenian Signal - Mendoza Straffon, Larissa (Frontiers in Psychology, 2021)
The fact that world-over people seem inexplicably motivated to allocate time and effort to apparently useless cultural practices, like the arts, has led several evolutionary scholars to suggest that these might be costly Zahavian signals correlated with genetic fitness, such as the infamous peacock’s tail. In this paper, I review the fundamental arguments of the hypothesis that art evolved and serves as a costly Zahavian signal. First, I look into the hypothesis that humans exert mate choice for indirect benefits and argue that the data supports mate choice for direct benefits instead. Second, I argue that art practice may well be a costly signal, however not necessarily related to good genes. Third, I suggest that Thorstein Veblen’s original concept of conspicuous signals as social tools to obtain and convey prestige provides a better account than the Zahavian model for the evolution and function of art in society. As a Veblenian signal, art could still have many of the effects suggested for visual art as a Zahavian signal, except not for the indirect benefits of optimal offspring, but for the direct benefits of acquiring and conveying social status.